Analysis Analysis of The Effect of Hot-Fit Models on Implementation of A Hospital Information System at Palangkaraya City Hospital - Astuti, Sri; Adikara, Fransiskus; Pamungkas, Rian Adi (Syntax Corporation, 2023)
This research is based on several problems faced by health workers in 2022 before SIRS is implemented and there are plans to implement SIRS in 2023. The aim of this research is to reveal empirically the influence of perceived benefits, quality of information, organizational support and work engagement on the implementation of SIRS. This research is included in quantitative research with a cross-sectional study design, the population used is 30 health workers, the sampling technique uses a saturated sample which makes the entire population as respondents. The analysis method uses the three box method and PLS-SEM with the help of the Smart-PLS program. The results of the analysis conclude that perceived benefits, quality of information and organizational support have a positive and significant effect both simultaneously and partially on the hospital information system, while work engagement has a negative effect on the implementation of the hospital information system.